Thermoreversible Hydrocolloid Blends for Structurally Stable Reheated Carrot Purée in Dysphagia Management - Narmatha Maran; Jorry Dharmawan; Kelvin K. T. Goh (Foods, 2025)
Oropharyngeal dysphagia is a common condition among older adults and individuals with neurological disorders, necessitating the use of texture-modified foods (TMFs) to ensure safe swallowing; however, reheating often leads to syneresis and structural breakdown, compromising both functionality and patient acceptability. This study aimed to evaluate the efficacy of single and binary hydrocolloid systems for improving the thermal and structural stability of moulded carrot purée formulated to meet International Dysphagia Diet Standardisation Initiative (IDDSI) Level 4 standards. The main methods involved preparing purées with various hydrocolloid combinations, assessing gel strength, shape retention, and syneresis following steaming, and validating results using commercial moulds. Thermoreversible methylcellulose (Benecel™ A4M) was the most effective single-component system, while binary blends of A4M with locust bean gum (LBG)—specifically B2 (1.5% A4M + 0.5% LBG) and B3 (1.5% A4M + 1% LBG)—demonstrated superior structural integrity, with height retention of 80 ± 2% (B2) and 85 ± 2% (B3), and reduced syneresis (~22 ± 1% and ~19 ± 3%, respectively; p < 0.05), both meeting IDDSI requirements. In contrast, formulations containing agar, xanthan, or carboxymethylcellulose exhibited poorer shape fidelity, likely due to matrix-disrupting interactions. These findings indicate that A4M-LBG blends offer a practical solution for producing reheatable, visually recognisable meals for individuals with moderate-to-severe dysphagia.